2017
DOI: 10.1364/ol.42.001023
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-basis tracking scheme for quantum key distribution using revealed sifted key bits

Abstract: Calibration of the polarization basis between the transmitter and receiver is an important task in quantum key distribution (QKD). An effective polarization-basis tracking scheme will decrease the quantum bit error rate (QBER) and improve the efficiency of a polarization encoding QKD system. In this paper, we proposed a polarization-basis tracking scheme using only unveiled sifted key bits while performing error correction by legitimate users, rather than introducing additional reference light or interrupting … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Compared to the approach of Ding et al [30], our approach has the advantage that only the reconciliation step is required to obtain sufficient information to run the polarization compensation algorithm. This allows for a greater tracking speed which is necessary to stabilize links with polarization drift of few Hz bandwidth.…”
Section: B Polarization Compensation Schemementioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the approach of Ding et al [30], our approach has the advantage that only the reconciliation step is required to obtain sufficient information to run the polarization compensation algorithm. This allows for a greater tracking speed which is necessary to stabilize links with polarization drift of few Hz bandwidth.…”
Section: B Polarization Compensation Schemementioning
confidence: 99%
“…Several approaches have been conceived to counteract these random polarization drifts, most of them requiring auxiliary laser pulses and complex time or wavelength multiplexing schemes [29], which add unwanted complexity to the QKD setups. A different approach was introduced by Ding et al that used the revealed portion of the sifted key [30], produced during the error correction and privacy amplification procedures, to detect and compensate the polarization drifts of the fiber link.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A different compensation scheme was proposed more recently that does not require any reference light signals [23,24]. In this scheme, one utilizes the number of erroneous bits in the revealed portion of the sifted keys during error correction process, which has to be monitored in a QKD protocol anyways to assess potential information leakage to an eavesdropper.…”
Section: Introductionmentioning
confidence: 99%
“…Polarization calibration is required in most QKD systems [7]- [11]. Considering an optical fiber channel, [8] used piezoelectric actuators to compensate the change of polarization, and [9] proposed a polarization-basis tracking scheme using sifted key bits revealed in the error correction step. Real-time continuous control was demonstrated based on a wavelengthdivision multiplexing method in [10].…”
Section: Introductionmentioning
confidence: 99%